MANAGEMENT SYSTEM FOR AVIATION SECURITY SUPPORT - Bezzubov, Dmytro O.; Khomyachenko, Svitlana I. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
In the article the problem of aviation security from the standpoint of administrative law. Identify the subjects and objects of aviation security. Establish the signs of this category. Proposed changes to the current legislation on ensuring safety management of aviation.